Implementation of Sasi which impact on the sustainability of ecosystem services in Maluku - Sahusilawane Maria M.; Sunardi; Iskandar Johan (E3S Web of Conferences, 2024)
Sasi is one of the local wisdom from Maluku as a form of prohibition for the community in taking natural products based on a certain time that has been determined by the authorized customary institution in an area. However, local wisdom is often ignored and considered outdated in the development of environmental conservation programs. Whereas in practice, armed with local knowledge capital such as biological and ecological knowledge, indigenous people have been able to successfully protect potential ecological processes and regenerate various varieties of plants and animals that are sasi. In addition, Sasi implementation activities can also have an impact on local ecosystem services so that the sustainability of local communities can take place economically, socially, culturally, and ecologically. The purpose of this research is to find out the implementation activities of Sasi and the ecosystem services that are produced sustainably for the people of Maluku. The method used in this research is a systematic literature review. The results of this study show that Sasi implementation activities have a positive impact on ecosystem services in an area.